House Fly, Musca Domestica L. (Diptera: Muscidae), Indices And Insecticide Resistance Profiles In Poultry Farms In Penang - Bong , Lee Jin (2010)

(untitled)
The present research was conducted to study the monthly changes in fly index and the insecticide resistance profiles in poultry farms. The information gathered can be used to formulate an effective control strategy for house fly. Changes in the index of the house fly, Musca domestica, was studied for a period of one year in two poultry farms in Penang, Malaysia: one in Balik Pulau, located on Penang Island, and the other in Juru, located on mainland Penang. The sampling of house flies was carried out from March 2007 to April 2008 by using the Scudder grill.